2015
DOI: 10.4172/2155-9627.1000205
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perceptions of Health Workers’ Training on Ethics, Confidentiality and Medico-Legal Issues

Abstract: Introduction Health care delivery in recent times has become more complicated, as patients expect health personnel to not only provide professional services but be accountable as well. It is thus imperative that health personnel are aware of their responsibility to the patient and also sensitive to medico legal issues if quality health care is to be assured. Objective The aim of the study was to assess the knowledge and perception of health care workers on their training in ethics, confidentiality and medico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 14 publications
3
16
0
Order By: Relevance
“…The socio-demographic characteristics of participants is as shown in Table 1 Discussion: The study revealed that the majority of the respondents had very good knowledge of ethics of professional practice and good knowledge of the regulatory roles of the Medical Rehabilitation Therapist Board-the regulatory body for the profession of physiotherapy. This finding is consistent with the findings by Barnie et al 4 ; Atila et al 10 and Arati and Bhagawati 11 that reported good knowledge of professional ethics among health workers, physiotherapists and nurses respectively.…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…The socio-demographic characteristics of participants is as shown in Table 1 Discussion: The study revealed that the majority of the respondents had very good knowledge of ethics of professional practice and good knowledge of the regulatory roles of the Medical Rehabilitation Therapist Board-the regulatory body for the profession of physiotherapy. This finding is consistent with the findings by Barnie et al 4 ; Atila et al 10 and Arati and Bhagawati 11 that reported good knowledge of professional ethics among health workers, physiotherapists and nurses respectively.…”
Section: Methodssupporting
confidence: 93%
“…3 The global trends in medico-legal issues and the growing public concern regarding the ethical conduct of healthcare professional demands a high level of professionalism among health care practitioners. 4 Physiotherapy as a profession in health care system provides services that develop, maintain, and restore maximum movement and functional ability throughout the lifespan of patients. 5 Physiotherapists constitute part of the multidisciplinary team in the management of the sick and mobility impaired persons, offering services in various settings (inpatient, outpatient, hospice, home) in order to alleviate the physical and functional aspects of the patient's suffering.…”
mentioning
confidence: 99%
“…Bernard Asamoah Barnie et al conducted a study on health care workers to check their knowledge and opinion regarding their training in ethics, confidentiality and medico-legal issues. They found that 74% had knowledge on ethics while in our study 86.11% students had the knowledge of Medical ethics (5).…”
Section: Gupta Et Al 359 Gmj 2019; 30: 358-360mentioning
confidence: 43%
“…Medication errors happen often when healthcare providers have insufficient knowledge about rules, modify rules or do not follow them in full [ 55 ]. Therefore, regular education to update knowledge and understanding of the medico-legal aspects of patient care is required to ensure quality of care [ 56 ]. All healthcare professionals have a duty to follow rules and regulations for safe medication practice.…”
Section: Discussionmentioning
confidence: 99%